2018
DOI: 10.1111/1759-7714.12768
|View full text |Cite
|
Sign up to set email alerts
|

Intrapleural combination therapy with lobaplatin and erythromycin for non‐small cell lung cancer‐mediated malignant pleural effusion

Abstract: BackgroundMalignant pleural effusion is a common complication of non‐small cell lung cancer (NSCLC); however, treatment options remain limited. This study evaluated the safety and efficacy of sequential intrapleural therapy with lobaplatin and erythromycin for NSCLC‐mediated malignant pleural effusion.MethodsFifty‐six patients with NSCLC complicated with malignant pleural effusion were recruited for a prospective single‐arm study from December 2014 to 2016; one patient dropped out. In addition to conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…These results suggest that if the drug is injected into the pleural cavity, the proportion of drug in blood will be low. In our study, the incidence of chest pain in the EG was higher than that of the ITG and CG, but chest pain was the main adverse reaction, and its incidence was consistent with that in our previous study (35.7%) 21 . There was no significant difference in the incidence of gastrointestinal reactions in patients in the EG, ITG, or CG.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results suggest that if the drug is injected into the pleural cavity, the proportion of drug in blood will be low. In our study, the incidence of chest pain in the EG was higher than that of the ITG and CG, but chest pain was the main adverse reaction, and its incidence was consistent with that in our previous study (35.7%) 21 . There was no significant difference in the incidence of gastrointestinal reactions in patients in the EG, ITG, or CG.…”
Section: Discussionsupporting
confidence: 91%
“…We previously used platinum and erythromycin to treat NSCLC patients with MPE. The short‐term ORR of MPE was 81.8%, which was consistent with the PE‐ORR of EG 21 . Animal experiments have shown that animals have pleural fibrosis after intrapleural injection of erythromycin, and clinical experiments have also shown that erythromycin is effective as a sclerosing agent for pleural adhesions 8,9 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“… 25 However, the efficiency of lobaplatin for the treatment of TNBC is largely unknown, although other studies have shown that it is beneficial for the treatment of non-small-cell lung cancer, colorectal cancer, nasopharyngeal carcinoma, and metastatic breast cancer. 16 , 27 29 Therefore, the present findings make an important contribution to what is known about the therapeutic effects of lobaplatin.…”
Section: Discussionmentioning
confidence: 53%
“…Han et al reported that low-dose interleukin-2 improved response rate and disease control rate in patients (89). Moreover, combination therapy with lobaplatin and erythromycin has been shown to be a safe and efficient treatment for patients with NSCLC-mediated MPE (90). A previous study demonstrated the low intensity of effusion immune cell PD-L1 expression in these neoplasms, which is associated with poor survival in patients with lung cancer (91).…”
Section: Discussionmentioning
confidence: 99%